Students' Perception About Merdeka Belajar Kampus Merdeka in Strengthening Their Skills - Rifari Baron; Diana Purwati; Heru Suparman; Rinovian Rais; Nurdin Nurdin (STAI Hubbulwathan Duri, 2023)
This research aims to get students' perspectives on the independent campus learning policy in strengthening their skills. The approach used is qualitative with a descriptive qualitative case study method. The process of collecting data used interviews, observations and group discussions. The informant is a postgraduate student at Indraprasta University, Jakarta, in the 2022-2023 academic year. The number of participants was 100 students. Data analysis uses stages of data reduction, data presentation, and conclusion. The results of the data analysis conclude that from a student perspective, implementing the independent campus learning policy requires adjustments that align with student needs and the global context. By implementing this policy, students become more independent to continue to improve their skills or potential. Apart from that, students can also develop 6C skills that are relevant to the educational needs of the 21st century. The results of this research have implications for the understanding of stakeholders in higher education institutions regarding the importance of understanding student perspectives in implementing independent campus learning curriculum policies.